Analisis Hubungan Usia dan Jenis Kelamin dengan Tingkat Distres Pada Pasien Diabetes Melitus Tipe 2 - Cendekia Airenda Muliandika; Gugun, Adang Muhammad; Alayyannur, Putri Ayuni (Fakultas Ilmu Keperawatan Universitas Klabat, 2025)
Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia resulting from impaired insulin secretion or insulin resistance. Type 2 DM is the most prevalent form, accounting for approximately 90–95% of all diabetes cases worldwide. In addition to causing physical complications, DM is also closely associated with psychological problems, one of which is distress. Distress in diabetic patients can increase blood glucose levels, exacerbate complications, and reduce quality of life. This study employed a descriptive observational design with a cross-sectional approach. The research instrument used was the Diabetes Distress Screening Scale (DDS), consisting of 17 questions. The study was conducted at PKU Muhammadiyah Gamping Hospital. The sample was obtained through purposive sampling, involving 47 type 2 DM patients who met the inclusion and exclusion criteria. Data were analyzed using the Kruskal–Wallis test with SPSS software. The majority of respondents experienced mild distress (63.8%), followed by moderate distress (29.8%) and severe distress (6.4%). The most influential domains were emotional burden and regimen-related distress, indicating that patients continue to face challenges in accepting their chronic condition and managing daily self-care routines. The Kruskal–Wallis analysis revealed no significant differences in distress levels based on gender (p=0.865) or age (p=0.912). In conclusion, most type 2 DM patients experienced mild distress, with no significant association between age or gender and distress levels. These findings highlight the importance of emotional support and continuous education to improve patients’ quality of life. Diabetes Melitus (DM) merupakan kelainan metabolik kronis yang ditandai oleh hiperglikemia akibat gangguan sekresi atau resistensi insulin. DM tipe 2 merupakan bentuk yang paling banyak diderita, mencapai hampir 90-95% dari seluruh kasus DM di dunia. Selain menimbulkan komplikasi fisik, DM juga berhubungan erat dengan masalah psikologis, salah satunya distres. Distres pada pasien DM dapat meningkatkan kadar gula darah, memperburuk komplikasi, dan menurunkan kualitas hidup. Penelitian ini menggunakan rancangan observasional deskriptif dengan desain cross-sectional. Instrumen penelitian berupa kuesioner Diabetes Distress Screening Scale (DDS) yang terdiri dari 17 pertanyaan. Penelitian dilaksanakan di RS PKU Muhammadiyah Gamping. Sampel penelitian diperoleh dengan teknik purposive sampling, didapatkan sebanyak 47 pasien DM tipe 2 yang memenuhi kriteria inklusi dan eksklusi. Analisis data dilakukan dengan uji Kruskal–Wallis menggunakan SPSS. Mayoritas responden mengalami distres ringan (63,8%), diikuti distres sedang (29,8%) dan distres berat (6,4%). Domain yang paling berpengaruh adalah beban emosional dan perawatan diri, yang menunjukkan bahwa pasien masih menghadapi kesulitan dalam menerima kondisi kronis serta mengelola rutinitas perawatan sehari-hari. Analisis Kruskal–Wallis tidak menemukan perbedaan bermakna tingkat distres berdasarkan jenis kelamin (p=0,865) maupun usia (p=0,912). Kesimpulanya sebagian besar pasien DM tipe 2 mengalami distres ringan. Usia dan jenis kelamin tidak berpengaruh secara signifikan dengan tingkat distres. Hasil penelitian ini menunjukkan pentingnya dukungan emosional dan edukasi berkelanjutan untuk meningkatkan kualitas hidup pasien.